Implementasi Wearable Device untuk Sistem Pendeteksi Stres pada Manusia berdasarkan Suhu Tubuh dan Detak Jantung - Izzati Firsta Wijayanti; Edita Rosana Widasari; Barlian Henryanu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Stress is the result of an unusual situation, with factors such as good or bad events, frustration, pressure, and environmental conditions causing stress. Stress can affect the condition of the body, and if a person experiences it, the body's reactions include excessive sweating, shaking, an increase in heart rate, rapid breathing, and headaches. Stress will be detected earlier and treated more effectively. As a result, we require a practical stress detector that is simple to use and can determine a person's condition based on his heart rate and body temperature. This stress detector uses two parameters: heart rate, which is detected by the MAX30102 sensor, and body temperature, which is measured by the MLX90614 sensor and processed by the Arduino Nano. The outcome of developing a tool with both sensors detecting via the fingers displayed on the OLED 0.96 inch and the accurarcy of the measurement between MLX90614 and thermometer is 98.51%, the measurement between MAX30102 and pulse oximeter got 92.43% accuracy and the overall test of the tool that has mad comparisons with DASS 42 stress scale got 70% accuracy using 10 subjects. The average computations time when a person detected as stress is 0.359 seconds.